The Level of Psychosocial Support of Parents for Children during Kindergarten (Raparin Journal of Humanities (RJH), 2023)
The objectives of this study are to realize the level of psychological and social support of parents through the study sample in general and to comprehend the level of psychological and social support based on some variables, such as gender of children, types of kindergarten (public or private), economic status of family. Thus, to achieve the aims of the study, a scale of 19 items was prepared with each section consisting of three options. After extracting the psychometric characteristics (reliability and validity), the research scale was carried out through interviews with the sample of 318 children between the ages of and (5-6) in the kindergartens of Ranya city. Later, the interview forms were collected and the results were analyzed using the SPSS program. The results revealed that the level of psychological and social support generally exists, and based on the variables, no major differences of psychosocial support were noticed in the study sample, except for the gender variable which was higher among girls. Finally, some recommendations and suggestions were presented.